2007
DOI: 10.1002/humu.20419
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in theC7orf11(TTDN1) gene in six nonphotosensitive trichothiodystrophy patients: no obvious genotype-phenotype relationships

Abstract: Trichothiodystrophy (TTD) is a rare autosomal recessive disorder whose defining feature is brittle hair. Associated clinical symptoms include physical and mental retardation of different severity, ichthyosis, premature aging, and, in half of the patients, photosensitivity. Recently, C7orf11 (TTDN1) was identified as the first disease gene for the nonphotosensitive form of TTD, being mutated in two unrelated cases and in an Amish kindred. We have evaluated the involvement of TTDN1 in 44 unrelated nonphotosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 17 publications
4
28
1
2
Order By: Relevance
“…Previous reports indicated that TTDN1 was mutated in patients with Amish brittle hair syndrome (ABSH) and in other non-photosensitive TTD cases with mental retardation and decreased fertility [25,37]. However, the physiological functions of TTDN1 were unknown.…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports indicated that TTDN1 was mutated in patients with Amish brittle hair syndrome (ABSH) and in other non-photosensitive TTD cases with mental retardation and decreased fertility [25,37]. However, the physiological functions of TTDN1 were unknown.…”
Section: Discussionmentioning
confidence: 93%
“…Nothing is currently known about the function of C7orf11/TTDN1, i.e. the gene mutated in a small proportion of non-photosensitive TTD cases that show normal response to UV-light and TFIIH steady state level [13,14]. To investigate which genes are mutated within the non-photosensitive form of TTD could lead to relevant information on the origin of the pathological TTD features in general.…”
Section: Concluding Remarks and Future Prospectivementioning
confidence: 98%
“…Mutations in the TTDN1 gene are associated with the nonphotosensitive form of TTD [13,14]. However, the majority of non-photosensitive TTD patients (approximately 80%) has not yet been linked with any causative gene.…”
Section: Trichothiodystrophymentioning
confidence: 98%
“…Allele-specific assays were carried out together with a control primer pair for the GAPDH gene [Botta et al, 2007] by quantification of allele-specific RT-PCR products as well as by real-time allele-specific RT-PCR. PCR reactions were set up in 20 ml using GeneSpin reagents (GeneSpin, Milano, Italy).…”
Section: Allele Specific Rt-pcrmentioning
confidence: 99%